History of Mathematics as a motivating topic in the teaching and learning process (Research, Society and Development, 2022)
This work consists of showing how advantageous it is to use the History of Mathematics as a motivating theme in the teaching and learning process. The present work aimed to understand that the History of Mathematics presented to students at the beginning of each mathematical content, can be a great ally of Mathematics teaching. A survey was carried out with students and teachers on the subject, seeking to verify if students have access to the History of Mathematics, if it is taught by teachers in the classroom and if there is an interest in the study of the History of Mathematics. A bibliographic study and two online questionnaires were used, one for teachers and another for students, which had multiple-choice and open-ended questions. The results were very significant, as the research showed that the students and teachers surveyed are aware of the importance of using the History of Mathematics and know how motivating it is and how it promotes significance for mathematical content.